Instrument choice and stranded assets in the transition to clean capital - Julie Rozenberg; Adrien Vogt-Schilb; Stephane Hallegatte (Inter-American Development Bank (IDB), 2017)
To mitigate climate change, some governments opt for instruments focused on investment, like performance standards or feebates, instead of carbon prices. We compare these policies in a Ramsey model with clean and polluting capital, irreversible investment and a climate constraint. Alternative instruments imply different transitions to the same balanced growth path. The optimal carbon price minimizes the discounted social cost of the transition to clean capital, but imposes immediate private costs that disproportionately affect the current owners of polluting capital, in particular in the form of stranded assets. A phased-in carbon price can avoid stranded assets but still result in a drop of income for the owners of polluting capital when it is implemented. Second-best standards or feebates on new investment lead to higher total costs but avoid stranded assets, preserve the revenues of vested interests, and smooth abatement costs over individuals and time. These results suggest a trade-off between political feasibility and cost-effectiveness of environmental policies.
Keywords: L50; O33; O44; Q52; Q54; Q58; 330; public acceptability; policy instrument; climate change; intergenerational equity; energy efficiency standards; mothballing; early-scrapping; premature retirement